JAK–STAT inhibition impairs K‐RAS‐driven lung adenocarcinoma progression. Issue 12 (10th September 2019) - Mohrherr, Julian; Haber, Marcel; Breitenecker, Kristina; Aigner, Petra; Moritsch, Stefan; Voronin, Viktor; Eferl, Robert; Moriggl, Richard; Stoiber, Dagmar; Győrffy, Balázs; Brcic, Luka; László, Viktória; et al.
Abstract : Oncogenic K‐RAS has been difficult to target and currently there is no K‐RAS‐based targeted therapy available for patients suffering from K‐RAS‐driven lung adenocarcinoma (AC). Alternatively, targeting K‐RAS‐downstream effectors, K‐RAS‐cooperating signaling pathways or cancer hallmarks, such as tumor‐promoting inflammation, has been shown to be a promising therapeutic strategy. Since the JAK–STAT pathway is considered to be a central player in inflammation‐mediated tumorigenesis, we investigated here the implication of JAK–STAT signaling and the therapeutic potential of JAK1/2 inhibition in K‐RAS‐driven lung AC. Our data showed that JAK1 and JAK2 are activated in human lung AC and that increased activation of JAK–STAT signaling correlated with disease progression and K‐RAS activity in human lung AC. Accordingly, administration of the JAK1/2 selective tyrosine kinase inhibitor ruxolitinib reduced proliferation of tumor cells and effectively reduced tumor progression in immunodeficient and immunocompetent mouse models of K‐RAS‐driven lung AC. Notably, JAK1/2 inhibition led to the establishment of an antitumorigenic tumor microenvironment, characterized by decreased levels of tumor‐promoting chemokines and cytokines and reduced numbers of infiltrating myeloid derived suppressor cells, thereby impairing tumor growth. Taken together, we identified JAK1/2 inhibition as promising therapy for K‐RAS‐driven lung AC. Abstract : What's new? A drug that inhibits the JAK–STAT pathway may score a hit against K‐RAS driven lung cancer. Here, the authors Investigated the JAK STAT pathway as a possible target in lung adenocarcinoma because of its role in inflammation‐mediated tumorigenesis. First, they showed that JAK1 and JAK2 are both activated in lung adenocarcinoma patients with oncogenic mutations in K‐RAS. Next, they treated the tumors with ruxolitinib, which inhibits JAK1/2. The drug successfully slowed tumor proliferation and progression in immunocompetent mouse models. Furthermore, treatment with ruxolitinib reduced the tumor‐promoting factors present in the microenvironment.